2021
DOI: 10.1186/s43058-021-00189-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategy fidelity evaluation for a multidisciplinary Chest Injury Protocol (ChIP)

Abstract: Background Blunt chest wall injuries can lead to complications, especially without early intervention. A blunt Chest Injury Protocol (ChIP) was developed to help improve the consistency of evidence-based care following admission to the emergency department. Implementation strategy fidelity is the extent to which the strategies of implementation are delivered in line with the intended plan. The aim of this study was to assess fidelity to the strategies of the implementation plan developed for Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Our instrumental case study assessment of fidelity to the ACT SMART Toolkit within ASD community agencies notably provides one of the first process models of assessing blended implementation strategy fidelity. Although a considerable amount of research has been conducted on intervention fidelity , few researchers have explored implementation strategy fidelity [ 37 , 52 , 53 ]. For example, Slaughter et al [ 37 ] found that no studies reporting on fidelity to implementation included a specific definition or theoretical framework for assessing implementation strategy fidelity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our instrumental case study assessment of fidelity to the ACT SMART Toolkit within ASD community agencies notably provides one of the first process models of assessing blended implementation strategy fidelity. Although a considerable amount of research has been conducted on intervention fidelity , few researchers have explored implementation strategy fidelity [ 37 , 52 , 53 ]. For example, Slaughter et al [ 37 ] found that no studies reporting on fidelity to implementation included a specific definition or theoretical framework for assessing implementation strategy fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Slaughter et al [ 37 ] conducted a scoping review that indicated no articles reporting fidelity to implementation strategies included definitions or conceptual frameworks for assessing implementation strategy fidelity. To our knowledge, few studies have examined fidelity to an implementation strategy and only one recent study has used a guiding theoretical framework [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our instrumental case study assessment of delity to the ACT SMART Toolkit and exploration of the potential relationship between delity and EBP use within ASD community agencies notably provide one of the rst models of assessing implementation strategy delity. Although a considerable amount of research has been conducted on intervention delity, few researchers have explored implementation strategy delity (35,49,50). For example, Slaughter et al (35) found that no studies reporting on delity to implementation included a speci c de nition or theoretical framework for assessing implementation strategy delity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Slaughter et al (35) conducted a scoping review that indicated no articles reporting delity to implementation strategies included de nitions or conceptual frameworks for assessing implementation strategy delity. To our knowledge, few studies have examined delity to an implementation strategy, and only one recent study has used a guiding theoretical framework (49,50).…”
mentioning
confidence: 99%